Determination of Total Phenolic Content and Antioxidant Activity of Epigallocatechin Gallate Rich Fraction from Tea Leaves (Camellia sinensis L.) - Puteri Amelia; Kinanti Citraningsih; Asri Kusuma Dewi; Vivi Anggia; Yuni Anggraeni (Fakultas Farmasi Universitas Andalas, 2025)
The tea plant, Camellia sinensis L., is a well-known natural product with significant health advantages. The main catechin found in green tea leaves is epigallocatechin gallate (EGCG), which has potent antioxidant properties. EGCG is a common active ingredient in products from the medical and cosmetics industries. This study examines the antioxidant properties and total phenolic content (TPC) of an EGCG-rich fraction (ERF) that is extracted from green tea leaves. TPC was quantified using the Folin-Ciocalteu method, with absorbance measured via UV-VIS spectrophotometry at 760.5 nm. Antioxidant activity was assessed using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, with absorbance recorded at 516 nm. The findings indicated that the TPC of ERF was 437.18 mg GAE/g ± 5.54, while the IC50 value for antioxidant activity was 4.47 mg/L, This value was lower than that of the positive control, Vitamin C, which exhibited an IC₅₀ of 5.07 mg/L. These results suggest that ERF could be developed into a natural ingredient for cosmetics and dietary supplements.